Non-Verbal Plural Number Agreement in the Cross-Linguistic Context: Combining Corpus Findings with Two Kinds of Acceptability Rating Results for English, German, Polish, and Czech - Rudnicka, Karolina; Klégr, Aleš (Nordic Journal of English Studies, 2024)
Non-verbal plural number agreement (manifested as the distributive plural or singular) is an under-researched topic, especially from a cross-linguistic perspective. English, German, Polish, and Czech appear to differ with regard to number preference in objects, PP adverbials and PP postmodifiers congruent with plural nouns (subjects, NP heads as antecedents). The present paper aims to comprehensively study this phenomenon, which has potential implications for language teaching, stylistic usage, translation, and language typology research. To achieve this, we combine evidence from the literature, corpus-based studies, and exploratory corpus searches with two kinds of acceptability ratings: Likert-scale questionnaires, completed by 400 participants, and forced-choice questionnaires, filled out by 120 participants. Hence, in addition to investigating the topic of non-verbal plural number agreement, our article offers methodological insights: it showcases how the results obtained from two kinds of acceptability ratings differ and complement each other and whether they reflect findings from corpora. Our findings confirm that English, German, Polish, and Czech vary in their preferences concerning non-verbal number agreement. These differences seem to be context- and noun-related. In particular, there are two scenarios in which, unlike English, the other languages prefer the distributive singular over the distributive plural: when the context is abstract and non-literal and when the singular is used to make a generic or generalized reference. Thus, we see the cross-linguistic differences as a language-specific rhetoric strategy.